Effects of plyometric training on technical skill performance among athletes: A systematic review and meta-analysis - Deng, N.; Soh, K. G.; Abdullah, B.; Huang, D.; Xiao, W.; Liu, H. (PLOS ONE, 2023)
Background The literature has proven that plyometric training (PT) improves various physical performance outcomes in sports. Even though PT is one of the most often employed strength training methods, a thorough analysis of PT and how it affects technical skill performance in sports needs to be improved.